Transient receptor potential vanilloid type 4 (TRPV4) promotes tumorigenesis via NFAT4 activation in nasopharyngeal carcinoma - Zhang, Peng; Li, Ke; Wang, Zhen; Wu, Yongjin; Zhang, Hua; Ma, Fang; Liu, Xiao-Yu; Tong, Michael C.F.; Ru, Xiaochen; Zhang, Xiangmin; Zeng, Xianhai (Frontiers in Molecular Biosciences, 2022)
Transient receptor potential vanilloid type 4 (TRPV4) can function as an oncogene or tumor suppressor depending on the tumor types. However, little is known regarding the effect of TRPV4 in nasopharyngeal carcinoma (NPC), a highly prevalent malignancy in Southern China and Southeast Asia. We found that TRPV4 mRNA and protein levels were significantly upregulated in NPC tissues. In addition, activation of TRPV4 in NPC cell lines using GSK1016790A (100 nM) induced a Ca2+ influx, whereas pharmacological inhibition or gene knockdown of TRPV4 reduced the proliferation rates of NPC cells. TRPV4 knockdown also decreased the growth of tumor xenografts in vivo. Mechanistically, TRPV4-mediated tumorigenesis is dependent on the activation of Ca2+/calcineurin/calcineurin-nuclear factor of activated T cell 4 (NFAT4) signaling. Furthermore, NFAT4 protein level was overexpressed in NPC tissues and correlated positively with TRPV4. Taken together, TRPV4 promotes the malignant potential of NPC cells by activating NFAT4 signaling. Our findings highlight TRPV4-NFAT4 axis as a potential therapeutic target in NPC.